Application of a photocatalyst with a magnetic covalent organic framework structure

By synthesizing magnetic Fe3O4 nanoparticles using a covalent organic frame and reacting with DMTP and TAPB to form a composite photocatalyst with a magnetic covalent organic frame structure, the existing catalyst heavy metal content and recovery difficulties were solved, and efficient and stable degradation effect of tetracycline hydrochloride was achieved.

CN118878004BActive Publication Date: 2025-04-15WUHAN UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410891293.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2025-04-15
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

Most existing catalysts contain heavy metals and have difficulties in the recycling process, making it difficult to develop photocatalytic oxidants with good recyclability and reusability, and will not cause secondary pollution to the environment.

Method used

Covalent organic frames (COFs) are used as raw materials to synthesize magnetic Fe3O4 nanoparticles by hydrothermal method and undergo amine-based treatment, and then react with DMTP and TAPB to form a composite photocatalyst with a magnetic covalent organic frame structure.

Benefits of technology

This magnetic covalent organic frame material can efficiently photocatalyze the degradation rate of tetracycline hydrochloride, with a degradation rate of more than 80%, and its photodegradation rate drops less after 5 cycles, and has good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118878004B_ABST
    Figure CN118878004B_ABST
Patent Text Reader

Abstract

The present invention relates to an application of a photocomposite catalyst of a magnetic covalent organic framework structure. The following steps are included: 1) synthesizing magnetic Fe3O4 nanoparticles by a hydrothermal method; 2) subjecting Fe3O4 to amination treatment; 3) reacting NH2-Fe3O4 with 2,5-dimethoxybenzene-1,4-diformaldehyde (DMTP) in acetonitrile; 4) adding 1,3,5-tris(4-aminophenyl)benzene (TAPB) for cross-linking reaction; 5) separating the target product. This highly efficient and reusable photocatalytic degradation material can be used to treat drug residues such as tetracycline hydrochloride (TC-HCl) in wastewater. The synthesis reaction is simple and the conditions are mild. When the light is irradiated for 5 minutes, the degradation rate of TC-HCl can reach 57.34%, proving that it has good photodegradation ability and good magnetic recovery performance. After experimental verification of the photocatalytic degradation of a simulated tetracycline hydrochloride solution, the photocomposite catalyst of the magnetic covalent organic framework exhibits good degradation performance and long-term stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalysts, and in particular to the application of an environmentally friendly, highly efficient and reusable photocatalytic degradation material. Background Art

[0002] With the continuous development of industry and human activities, many serious problems have been brought to the environment, among which wastewater pollution is the focus of people's attention. Therefore, most scientific researchers are constantly trying various innovative technologies in order to find environmentally friendly and efficient wastewater treatment methods. In particular, the research on pharmaceutical wastewater has attracted widespread attention because these wastewaters contain a large amount of antibiotics, which may cause great harm to humans and the environment. Among them, tetracycline antibiotics, especially tetracycline hydrochloride, have become the focus of research. This antibiotic is widely used in agriculture, fisheries and animal husbandry, and is even used as a growth promoter. However, a large amount of tetracycline hydrochloride is released into the aquatic environment, resulting in increased resistance of microorganisms to antibiotics, thereby destroying the ecological balance and posing a threat to human health.

[0003] In order to solve this problem, scholars have continuously developed water treatment technologies, such as adsorption, membrane separation, biotechnology and advanced oxidation processes (AOPs). Among them, AOPs have attracted much attention due to their high efficiency and no secondary pollution. AOPs effectively oxidize organic pollutants in water by producing various free radicals and degrade them into harmless substances. Therefore, studying the removal method of tetracycline hydrochloride in water has become a hot issue at home and abroad.

[0004] However, most existing catalysts contain heavy metals and are harmful to the environment, and there are also difficulties in the recycling process. Therefore, there is an urgent need to develop photocatalytic oxidants with good recyclability and reusability, and without causing secondary pollution to the environment.

[0005] In this context, covalent organic frameworks (COFs) have emerged and attracted much attention due to their strong chemical and mechanical properties, inherent porosity, and unique ordered channel structure. The well-defined crystalline porous structure and customized functions of COFs offer great potential for various applications such as adsorption, chemical sensing, and environmental remediation. This new type of material may become an important tool for solving water treatment problems in the future and create a cleaner and healthier environment for mankind. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides an environmentally friendly, efficient and reusable magnetic covalent organic framework prepared by using a covalent organic framework as a raw material. The magnetic covalent organic framework prepared by the method has good photocatalytic degradation of tetracycline hydrochloride, and the preparation method is simple, easy to control, thermostatic and environmentally friendly.

[0007] The present invention proposes a method for preparing a composite photocatalyst with a magnetic covalent organic framework structure, which specifically comprises the following preparation steps:

[0008] Step 1, synthesizing magnetic Fe3O4 nanoparticles by hydrothermal method;

[0009] The specific steps are as follows:

[0010] ① Weigh 2.703 g (10 mmol) Fe(NO3)3·9H2O, dissolve in 80 mL ethylene glycol, and stir vigorously at room temperature until clear;

[0011] ②Add 2g polyethylene glycol and 7.2g sodium acetate and continue stirring until completely dissolved;

[0012] ③ The mixture was transferred to a 100 mL Teflon stainless steel high temperature reactor and subjected to hydrothermal reaction at 200 °C for 24 h;

[0013] ④ After the hydrothermal reaction is completed and the reactor is naturally cooled to room temperature, the supernatant is discarded, the black precipitate is collected by a strong magnet, and washed with deionized water and anhydrous ethanol several times;

[0014] ⑤Finally, place it in a vacuum drying oven and dry it at 60°C for 12 hours to obtain the sample.

[0015] Step 2, the synthesized magnetic Fe3O4 nanoparticles are subjected to an amination treatment;

[0016] The specific steps are as follows:

[0017] ① Add 500 mg Fe3O4 to 50 mL anhydrous ethanol and ultrasonicate for 60 min to obtain solution A;

[0018] ② Add 300 μL APTES to 10 mL anhydrous ethanol and stir well to prepare solution B.

[0019] ③ Slowly add liquid B to liquid A while stirring vigorously, and then continue stirring for 2 hours;

[0020] ④ The product was then repeatedly washed with deionized water and anhydrous ethanol, and the precipitate was separated by high-speed centrifugation.

[0021] ⑤Finally, place the precipitate in a vacuum drying oven and dry it at 60°C for 12 hours to obtain a sample.

[0022] Step 3: Prepare the composite catalyst material with magnetic covalent organic framework structure by reacting NH2-Fe3O4 with DMTP in acetonitrile; then, add TAPB for cross-linking reaction and let stand at room temperature for 72 hours; finally, wash the product three times with N-dimethylformamide, tetrahydrofuran and anhydrous ethanol respectively, and separate the magnetic covalent organic framework by high-speed centrifugation. Specifically, it includes the following steps:

[0023] ① Add 60 mg of aminated Fe3O4 nanoparticles and DMTP into a centrifuge tube, then add 37.5 mL of acetonitrile, an organic regulator, and sonicate for 10 min until complete fusion;

[0024] ② Weigh a certain amount of TAPB and add it to the mixed solution in step ① and perform ultrasonic treatment for 5 minutes;

[0025] ③ Add 2.25 mL of 12 M HAc, an organic regulator, to the mixed solution in step ② to carry out a cross-linking reaction for 72 hours;

[0026] ④Finally, the precipitate in step ③ was separated by high-speed centrifugation, and then DMF, THF and anhydrous ethanol solutions were added for repeated washing, and vacuum dried at 60°C for 12 hours to obtain a sample;

[0027] The molar ratio of DMTP to TAPB is 3:2.

[0028] The present invention also proposes to apply the catalyst prepared above to the degradation of tetracyclic antibiotics.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The magnetic covalent organic framework material Fe3O4@TAPB-DMTP-COF of the present invention takes iron as the core, connects aldehyde monomers to the amino groups on the periphery of iron, and further connects amino monomers to the aldehyde groups, forming a flower ball-like structure composed of flat sheets, with an overall size of 350-400nm and a shell thickness of 75nm.

[0031] 2. The magnetic covalent organic framework material Fe3O4@TAPB-DMTP-COF, on the one hand, utilizes the high adsorption performance of TAPB-DMTP-COF, and on the other hand, combines COF to produce hydrogen peroxide after light exposure. The iron-based material and hydrogen peroxide can undergo Fenton reaction to generate free radicals, which are highly oxidizing and can oxidize organic pollutants. The formation of -OH free radicals will cause the ketone group, double bond, and amino group of the TC molecule to break. Therefore, under light, it can synergistically play the role of degrading large molecular pollutants in wastewater.

[0032] 3. The magnetic covalent organic framework material Fe3O4@TAPB-DMTP-COF can be used for the photocatalytic degradation of tetracycline hydrochloride in wastewater, degrading tetracycline hydrochloride in the water into low-toxic small molecular compounds until it is completely mineralized into water and carbon dioxide. After 30 minutes of illumination, the degradation rate reached more than 80%, and after 5 cycles, its photodegradation rate decreased less, showing good stability.

[0033] 4. This material is a photocatalytic material with good degradation effect, environmental friendliness, simple production process and abundant raw materials. It has good research and application prospects in environmental protection and has huge economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 XRD diffraction patterns of synthesized TAPB-DMTP-COF, amination Fe3O4, and Fe3O4@TAPB-DMTP-COF materials.

[0035] Figure 2 These are the infrared absorption spectra of synthetic monomer TAPB, synthetic monomer DMTP, amination Fe3O4, Fe3O4@TAPB-DMTP-COF and synthetic TAPB-DMTP-COF.

[0036] Figure 3 Scanning electron microscope images of amination Fe3O4 at different magnifications.

[0037] Figure 4 Scanning electron microscope images of TAPB-DMTP-COF at different magnifications.

[0038] Figure 5 Scanning electron microscope images of Fe3O4@TAPB-DMTP-COF at different magnifications.

[0039] Figure 6 Schematic diagram of the recovery of Fe3O4@TAPB-DMTP-COF catalyst in water by magnet.

[0040] Figure 7 The figure is a fitting curve diagram of the determination of tetracycline hydrochloride by ultraviolet absorption spectrophotometry, wherein (a) is the ultraviolet absorption spectrum of 1-5 mg / L tetracycline hydrochloride, and (b) is the fitting curve diagram of the concentration of tetracycline hydrochloride and the corresponding absorbance.

[0041] Figure 8The degradation dynamic curves of Fe3O4@TAPB-DMTP-COF and TAPB-DMTP-COF catalysts in the visible light range for photodegradation of tetracycline hydrochloride; wherein, a is the adsorption-photodegradation dynamic curve, b is the photodegradation dynamic curve, c is the photodegradation dynamic bar chart, and d is a comparison chart of the five-cycle degradation of Fe3O4@TAPB-DMTP-COF. Specific implementation methods

[0042] Example 1

[0043] 1) Preparation of magnetic Fe3O4 nanoparticles;

[0044] ① Weigh 2.703 g (10 mmol) Fe(NO3)3·9H2O, dissolve in 80 mL ethylene glycol, and stir vigorously at room temperature until clear;

[0045] ②Add 2g polyethylene glycol and 7.2g sodium acetate and continue stirring until completely dissolved;

[0046] ③ The mixture was transferred to a 100 mL Teflon stainless steel high temperature reactor and subjected to hydrothermal reaction at 200 °C for 24 h;

[0047] ④ After the hydrothermal reaction is completed and the reactor is naturally cooled to room temperature, the supernatant is discarded, the black precipitate is collected by a strong magnet, and washed with deionized water and anhydrous ethanol several times;

[0048] ⑤Finally, place it in a vacuum drying oven and dry it at 60°C for 12 hours to obtain the sample.

[0049] 2) Amination treatment of Fe3O4 nanoparticles;

[0050] ① Add 500 mg Fe3O4 to 50 mL anhydrous ethanol and ultrasonicate for 60 min to obtain solution A;

[0051] ② Add 300 μL APTES (3-aminopropyltriethoxysilane) to 10 mL anhydrous ethanol and stir well to prepare solution B.

[0052] ③ Slowly add liquid B to liquid A while stirring vigorously, and then continue stirring for 2 hours;

[0053] ④ The product was then repeatedly washed with deionized water and anhydrous ethanol, and the precipitate was separated by high-speed centrifugation;

[0054] ⑤Finally, place the precipitate in a vacuum drying oven and dry it at 60°C for 12 hours to obtain a sample.

[0055] 3) Magnetic covalent organic frameworks;

[0056] ① Add 60 mg of aminated Fe3O4 nanoparticles and 87 mg of DMTP (2,5-dimethoxybenzene-1,4-dicarboxaldehyde) to multiple 50 mL centrifuge tubes, add 37.5 mL of acetonitrile, and sonicate for 10 min until complete fusion;

[0057] ② Weigh 105 mg of TAPB (1,3,5-tris(4-aminophenyl)benzene) and add it to the mixed solution in step ① and perform ultrasonic treatment for 5 minutes;

[0058] ③ Add 2.25 mL of 12 M HAc to the mixed solution in step ② and perform a cross-linking reaction for 72 h;

[0059] ④Finally, the precipitate in step ③ was separated by high-speed centrifugation. Then, DMF (N, N-dimethylformamide), THF (tetrahydrofuran) and anhydrous ethanol solution were added for repeated washing, and vacuum dried at 60°C for 12 hours to obtain a sample, namely the magnetic covalent organic framework catalyst material Fe3O4@TAPB-DMTP-COF.

[0060] Example 2

[0061] The preparation method of TAPB-DMTP-COF material without adding Fe3O4 is as follows:

[0062] ① 87 mg DMTP (2,5-dimethoxybenzene-1,4-dicarboxaldehyde), add 37.5 mL acetonitrile, and sonicate for 10 min until completely fused;

[0063] ② Weigh 105 mg of TAPB (1,3,5-tris(4-aminophenyl)benzene) and add it to the mixed solution in step ① and perform ultrasonic treatment for 5 minutes;

[0064] ③ Add 2.25 mL of 12 M HAc to the mixed solution in step ② and perform a cross-linking reaction for 72 h;

[0065] ④Finally, the precipitate in step ③ was separated by high-speed centrifugation. Then, DMF (N, N-dimethylformamide), THF (tetrahydrofuran) and anhydrous ethanol solution were added for repeated washing, and vacuum dried at 60°C for 12 hours to obtain a sample, i.e., TAPB-DMTP-COF material without adding Fe3O4.

[0066] The Fe3O4 nanoparticles treated with amino in step 2) of Example 1, the magnetic covalent organic framework material Fe3O4@TAPB-DMTP-COF obtained in step 3), and the TAPB-DMTP-COF material without adding Fe3O4 prepared in Example 2 were subjected to structural characterization tests, and XRD diffraction patterns were obtained, as shown in FIG. Figure 1As shown in the upper right corner box in the figure, the main diffraction peaks of TAPB-DMTP-COF are concentrated at 5.6°, 7.4°, 9.7° and 25.4°, corresponding to the (200), (210), (220) and (001) reflection planes. The diffraction pattern of Fe3O4@TAPB-DMTP-COF shows obvious peaks at 30.3°, 35.7°, 43.2°, 53.6°, 57.2° and 62.8°. These peaks belong to Fe3O4 (PDF#19-0629). Since TAPB-DMTP-COF is coated on the surface of Fe3O4 and the amount of Fe3O4 added is small, the peak intensity of Fe3O4 is weak. The results show that Fe3O4@TAPB-DMTP-COF was successfully synthesized.

[0067] The Fe3O4 nanoparticles treated with amino in step 2) of Example 1, the magnetic covalent organic framework material Fe3O4@TAPB-DMTP-COF obtained in step 3), the TAPB-DMTP-COF material without adding Fe3O4 prepared in Example 2, and the TAPB alone and DMTP alone were tested by infrared absorption spectroscopy. The results are as follows: Figure 2 As shown, monomer DMTP is at 1682 cm -1 The absorption peak of monomer TAPB is 3355cm -1 and 1621cm -1 There is a strong absorption peak at 586cm, corresponding to the -N=H functional group; Fe3O4 -1 There is an obvious absorption peak at 1592 cm, which corresponds to the vibration of Fe-O bond. In addition, TAPB-DMTP-COF and Fe3O4@TAPB-DMTP-COF have -1 There is an absorption peak at , which corresponds to the -C=N functional group.

[0068] The Fe3O4 nanoparticles treated with amino in step 2) of Example 1, the magnetic covalent organic framework material Fe3O4@TAPB-DMTP-COF obtained in step 3), and the TAPB-DMTP-COF material without adding Fe3O4 prepared in Example 2 were scanned by electron microscope at different magnifications, as shown in FIG. Figure 3 As shown in the figure, the morphology of the aminated Fe3O4 is spherical with depressions, and the size is between 200-250nm. Figure 4 The morphology of TAPB-DMTP-COF is uniform, consisting of flat sheets in a flower ball shape with a size of 200-250nm. Figure 5It can be found that the size of Fe3O4@TAPB-DMTP-COF is larger than that of Fe3O4 and TAPB-DMTP-COF, and is about 350-400nm, which indicates that Fe3O4 is successfully encapsulated inside TAPB-DMTP-COF. Figure 6 It can be seen that the synthesized Fe3O4@TAPB-DMTP-COF can be adsorbed by the magnet, which further indicates that the material can maintain its magnetic properties.

[0069] Example 3

[0070] The photocatalytic performance test of the catalysts prepared in Example 1 and Example 2 for degrading tetracycline hydrochloride was carried out to investigate the photodegradation activity of the synthesized catalysts. The specific steps are as follows:

[0071] 5 mg of the magnetic covalent organic framework structure was added to 50 mL of tetracycline hydrochloride solution of different concentrations and ultrasonically homogenized. The cooling circulating water temperature was adjusted to 25°C. Without adjusting the pH, the solution was stirred and adsorbed for 30 minutes in the dark to reach adsorption-desorption equilibrium. The solution was then illuminated for 30 minutes. During the illumination process, 3 mL of the reaction solution was taken every 5 minutes and filtered with a 0.22 μm filter. The concentration of tetracycline hydrochloride at different illumination times was determined by ultraviolet spectrophotometry. The illumination conditions were: tetracycline hydrochloride was degraded under irradiation with a 300 W xenon lamp (filter cutoff wavelength 420 nm).

[0072] The concentration of tetracycline hydrochloride was determined by ultraviolet-visible spectrophotometer (UV-1200).

[0073] The pollutant removal rate calculation formula is:

[0074] Removal rate (%) = (1-C / C0) × 100%;

[0075] Among them, C is the pollutant concentration at time t, and C0 is the initial pollutant concentration.

[0076] Degradation tests were conducted on tetracycline hydrochloride at different concentrations (including 1 mg / L, 2 mg / L, 3 mg / L, 4 mg / L, and 5 mg / L). Figure 7 As shown in (a), as the concentration of tetracycline hydrochloride increases, the absorbance gradually increases; Figure 7 In (b), a scatter plot is made between the absorbance and concentration at the characteristic peak of tetracycline hydrochloride at 357 nm, and then a linear regression equation of absorbance and concentration is obtained by fitting. The regression coefficient is 0.99943. Therefore, the concentration of tetracycline hydrochloride can be determined by UV-visible spectrophotometry.

[0077] The photocatalytic degradation efficiency of the catalyst prepared in Example 1 and Example 2 was tested for tetracycline hydrochloride with a concentration of 20 mg / L according to the above photocatalytic reaction steps. The results are as follows: Figure 8 shown.

[0078] like Figure 8 As shown in the figure, the degradation rate of Fe3O4@TAPB-DMTP-COF under the same illumination time is greater than that of TAPB-DMTP-COF. Figure 8 (d) shows that the photodegradation rate of Fe3O4@TAPB-DMTP-COF decreased less after 5 cycles, indicating that it has good stability.

[0079] In the absence of light, the degradation efficiency of TAPB-DMTP-COF prepared in Example 2 is slightly greater than that of Fe3O4@TAPB-DMTP-COF prepared in Example 1. After the start of light irradiation, the degradation efficiency of Fe3O4@TAPB-DMTP-COF prepared in Example 1 is significantly improved. This is because, before illumination, the adsorption of tetracycline hydrochloride depends on the adsorption performance of the catalyst material. As mentioned above, the amination Fe3O4 is a spherical shape with a size of 200-250nm and a depression, and TAPB-DMTP-COF is a flower ball with a uniform morphology and a size of 200-250nm. The size of Fe3O4@TAPB-DMTP-COF is larger than that of Fe3O4 and TAPB-DMTP-COF, and is a flower ball with a size of about 350-400nm. Flat sheets grow on the periphery of the inner core Fe3O4 and gradually extend to form a shell with a thickness of about 75nm. At this time, the pore structure of Fe3O4@TAPB-DMTP-COF becomes smaller, so its adsorption performance becomes weaker, and the pore structure of TAPB-DMTP-COF is not as large as that of TAPB-DMTP-COF. The degradation efficiency of TAPB-DMTP-COF prepared in Example 2 is slightly greater than that of Fe3O4@TAPB-DMTP-COF prepared in Example 1.

[0080] After the illumination, the degradation efficiency of Fe3O4@TAPB-DMTP-COF prepared in Example 1 was significantly improved. This is because the addition of Fe3O4 produces a partial Fenton effect, COF can produce hydrogen peroxide after illumination, and the iron-based material and hydrogen peroxide can undergo a Fenton reaction to generate free radicals, which have strong oxidizing properties and can oxidize organic pollutants. The formation of ·OH free radicals will cause the keto group, double bond, and amino group of the TC molecule to break.

Claims

1. Application of a composite photocatalyst with a magnetic covalent organic framework structure in the degradation of tetracyclic antibiotics, characterized in that: The preparation method of the catalyst comprises the following preparation steps: 1) preparing magnetic iron-containing nanoparticles, wherein the iron-containing nanoparticles are Fe3O4 nanoparticles; 2) Amination treatment of nanoparticles containing iron elements to obtain aminated Fe3O4 nanoparticles, the treatment steps are as follows: ① Add Fe3O4 nanoparticles into anhydrous ethanol and ultrasonicate for 60 min to form liquid A; ② Add 3-aminopropyltriethoxysilane APTES to anhydrous ethanol and stir evenly to prepare liquid B; ③ Slowly add solution B to solution A while stirring vigorously, and then continue stirring for 2 hours; ④ The product was then repeatedly washed with deionized water and anhydrous ethanol, and the precipitate was separated by high-speed centrifugation; 3) preparing a composite catalyst material with a magnetic covalent organic framework structure, uniformly mixing the aminated iron-containing nanoparticles and aldehyde monomers in an organic regulator 1, then adding amine monomers, obtaining a mixed solution after ultrasonic reaction, then adding organic regulator 2 to the mixed solution to promote cross-linking reaction, and finally separating and drying the cross-linking reaction product to obtain a magnetic covalent organic framework structure catalyst material Fe3O4@TAPB-DMTP-COF, wherein the magnetic covalent organic framework structure catalyst material has Fe3O4 as the core, aldehyde monomers are connected to the amine groups on the periphery of iron, and amine monomers are further connected to the aldehyde groups to form a flower ball-like structure composed of flat sheets with an overall size of 350-400 nm, and the flat sheets grow on the periphery of the inner core Fe3O4 and gradually extend to form a shell layer with a thickness of 75 nm; The aldehyde monomer in step 3) is 2,5-dimethoxyterephthalaldehyde DMTP; The amine monomer in step 3) is 1,3,5-tris(4-aminophenyl)benzene TAPB; The organic regulator in step 3) is acetonitrile; The second organic regulator in step 3) is acetic acid; In the step 3), the molar ratio of the aldehyde group in the aldehyde monomer to the amino group in the amine monomer is 1:1; The amount of the iron-containing nanoparticles subjected to amination treatment in step 3) is in the range of 30-120 mg.

2. The use according to claim 1, characterized in that: The preparation steps of the Fe3O4 nanoparticles are as follows: ① Weigh 2.703 g Fe(NO3)3·9H2O, dissolve it in 80 mL ethylene glycol, and stir vigorously at room temperature until the solution becomes clear; ② Add 2 g polyethylene glycol and 7.2 g sodium acetate, continue stirring until completely dissolved to obtain a mixed solution; ③ The mixture was transferred to a 100 mL Teflon stainless steel high temperature reactor and subjected to hydrothermal reaction at 200 °C for 24 h; ④ After the hydrothermal reaction is completed and the reactor is naturally cooled to room temperature, the supernatant is discarded, the black precipitate is collected by a strong magnet, and then washed with deionized water and anhydrous ethanol several times; ⑤ Finally, place it in a vacuum drying oven and dry it at 60 ℃ for 12 h to obtain the sample.

3. The use according to claim 1, characterized in that: The specific steps of step 3) are as follows: 3) Magnetic covalent organic frameworks; ① Add aminated Fe3O4 nanoparticles and DMTP into a centrifuge tube, then add organic regulator 1, and ultrasonicate for 10 minutes until complete fusion; ② Weigh a certain amount of TAPB and add it to the mixed solution in step ① for ultrasonic treatment for 5 min; ③ Adding organic regulator 2 to the mixed solution in step ② to carry out a cross-linking reaction for 72 h; ④ Finally, the precipitate in step ③ was separated by high-speed centrifugation, and then DMF, tetrahydrofuran and anhydrous ethanol solutions were added for repeated washing, and vacuum dried at 60 ° C for 12 h to obtain a sample; The molar ratio of DMTP to TAPB is 3:2; the first organic regulator is 37.5 mL of acetonitrile, the second organic regulator is 2.25 mL of 12M HAc, and the mass of the aminated Fe3O4 nanoparticles is 60 mg.

4. The use according to claim 1, characterized in that: The tetracycline antibiotic is tetracycline hydrochloride.

Citation Information

Patent Citations

  • Preparation method and applications for magnetic covalent organic frame material

    CN110090624A

  • Preparation method of covalent organic framework sponge composite material, obtained product and application of product in photocatalytic degradation of antibiotics

    CN113231100A